REFERENCE ERROR IN BOOK MANUSCRIPT FROM LIPI: HOW GOOD OUR SCIENTISTS ARE IN COMPOSING REFERENCES - Helmiawan, Martinus (BACA: Jurnal Dokumentasi dan Informasi, 2025)
Reference lists from 13 book manuscripts that were submitted to LIPI Press in 2018 written by the writers from LIPI were examined. In total, there were 879 reference list entries, and the accuracy of each citation was examined. The examination was conducted by firstly determining the type of error and reference style used for cross-checking. Afterwards, each entry was thoroughly checked for errors. Found errors were grouped into each type of error. The result, only 100 entries were error-free, and from the 779 entries that contain errors, 3,651 errors were found. The errors were categorized into 1,576 punctuation errors; 396 capitalization errors; 338 italicization errors, 206 spelling and word choice errors; 126 syntax errors; 642 spacing errors; 46 extraneous information errors; and 321 missing data errors. From that result, error rate of 4.15 was achieved. This paper concluded that the overall huge error rate found shows the negligence of the writers in composing references.